2016
DOI: 10.1007/s00426-016-0753-6
|View full text |Cite
|
Sign up to set email alerts
|

Keep it cool: temperature priming effect on cognitive control

Abstract: The effect of physical temperature on cognition and behavior has been the focus of extensive research in recent years, demonstrating that embodied concepts are grounded in, and shaped by, sensorimotor physical experiences. Nevertheless, less is known about how experienced and perceived temperatures affect cognitive control, one of humans core executive functions. In the present work, we primed participants with cool versus warm temperature using a between participants manipulation of physical touch experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 76 publications
0
21
0
1
Order By: Relevance
“…In another study (Ho et al, 2014b ), the results indicated that visual information can affect thermal discrimination RTs, but thermal cues did not influence color discrimination responses. Halali et al ( 2017 ) showed that cool compared to warm temperature priming (participants were primed using touch experience and by viewing pictures of landscapes) improved cognitive control performance, and such a temperature priming effect does not necessarily require a physical touch experience. Although more elaborate research is needed to confirm whether there is a bidirectional mechanism of visual processing and thermal sensation, it is also possible temperature stimulation influenced the processing of visual information (including but not necessarily limited to higher level semantic processing).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study (Ho et al, 2014b ), the results indicated that visual information can affect thermal discrimination RTs, but thermal cues did not influence color discrimination responses. Halali et al ( 2017 ) showed that cool compared to warm temperature priming (participants were primed using touch experience and by viewing pictures of landscapes) improved cognitive control performance, and such a temperature priming effect does not necessarily require a physical touch experience. Although more elaborate research is needed to confirm whether there is a bidirectional mechanism of visual processing and thermal sensation, it is also possible temperature stimulation influenced the processing of visual information (including but not necessarily limited to higher level semantic processing).…”
Section: Discussionmentioning
confidence: 99%
“…Inagaki and Eisenberger ( 2013 ) showed that people feel more “connected” after holding a warm object and warmer after reading positive messages; and feelings of belonging were found to be threatened when people with low family support drink cold water (Chen et al, 2014 ). Moreover, the experience of cold temperatures even improves the performance of an anti-saccade task, as “cold behavior” is a concept used to describe rational and deliberate behavior (Halali et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…After answering a few demographic questions, participants were randomly assigned to one of the two manipulation conditions: heat versus control. In the heat manipulation condition, participants were asked to “recall a time when they felt uncomfortably hot.” To help participants in the recall task and consistent with prior studies using pictures to prime temperature, they were also provided with several pictures of people suffering from heat (e.g., Halali, Meiran, & Shalev, ; Wilkowski, Meier, Robinson, Carter, & Feltman, ). Participants were then asked to close their eyes and truly engage in the recall experience for 1 minute and then write down the details of the incident and the feelings associated with the heat in the space provided.…”
Section: Methodsmentioning
confidence: 99%
“…Think of lab temperature. Although previous research has already indicated temperature to be of crucial importance to basic cognitive processes (e.g., Halali, Meiran, & Shalev, 2016;IJzerman & Semin, 2009;IJzerman & Hogerzeil, 2017), very few Stroop tasks have controlled for lab temperature in their design. With our conditional random forest approach, it becomes clearer and clearer how important temperature is for basic cognitive functioning (cf.…”
Section: Discussionmentioning
confidence: 99%